The Effect of Sape Music on Salivary Flow Rate - Salsabillah Syarifahdani; Shanty Chairani; Rinda Yulianti (Sriwijaya Journal of Dentistry, 2026)
Introduction: Hyposalivation can negatively impact oral health, so the flow rate of saliva needs to be increased. Music with a calm and peaceful atmosphere has been shown to increase the salivary flow rate. Purpose: This study aims to evaluate the effect of Sape music on salivary flow rate. Methods: This study used quasi-experimental research with a one-group pretest-posttest approach involving 20 students from the Dentistry Study Program, Faculty of Medicine, Sriwijaya University. Unstimulated saliva was collected in the morning before listening to music using the spitting method for 5 minutes. Subjects were presented with Sape music stimuli for 15 minutes. and during the final 5 minutes of the music session, saliva was collected again using the same spitting method. The collected saliva was recorded as the salivary flow rate in g/minute. Data were analyzed using a parametric paired T-test and were considered significant if the p-value <0,05. Result: The result showed that the mean of salivary flow rate after listening to Sape music was 0,411± 0,142 g/minute, which was higher than before lisitening, which was  0,558±0,135 g/minute.  The paired T-test analysis showed a significant difference in salivary flow rate before and after listening to Sape music which the p-value was 0,001 (p<0,05). Conclusion: Sape music can increase the salivary flow rate.